Three-dimensional evaluation of the tongue volume in different dentoskeletal patterns - A cone beam computed tomographic study - Seema Grover; Maninder Singh Sidhu; Gowri Sankar Singaraju; Ashish Dabas; Namrata Dogra; Munish Midha (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study is to evaluate tongue volume using cone-beam computed tomographic (CBCT) and its correlation to different growth patterns in patients. Materials and Methods: Sixty preorthodontic records of CBCT scans of subjects ranging from 14 to 25 age group from retrospective data of department were selected for the study. Patients were classified into three groups based on angle FMA; Group I (n = 20) with average growth pattern (FMA 22°-28°); Group II (n = 20) vertical growth pattern (FMA >28°); Group III (n = 25) horizontal growth pattern (FMA <20°). Tongue volume evaluation was done using Myrian® Software. Dentoskeletal features and parameters related to archform such as palatal vault depth, interpremolar, and intermolar distance were evaluated in all the subjects. ANOVA test was used for intergroup comparison of tongue volume and dentoskeletal parameters in all three groups. Correlation of the tongue volume to dentoskeletal parameters was done using Pearson's correlation test. Results: Mean tongue volume in Group I was 66.10 cm3, Group II, 66.04 cm3 and Group III was 66.72 cm3. There was a statistically significant correlation (P < 0.5) of tongue volume with palatal vault width, maxillary length, and mandibular interpremolar and intermolar distance among dentoskeletal parameters. Conclusion: Tongue volume was found equal in all groups despite the variation in growth patterns. Skeletal differences leading to different growth patterns were found to be related to mandibular morphology. The results indicate the indirect role of the tongue in causing malocclusion in orthodontic patients.